2000
DOI: 10.1097/00000372-200008000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Solitary Keratoacanthoma

Abstract: To discuss the relation between solitary keratoacanthoma (KA) and crateriform squamous cell carcinoma (cSCC), the clinical and histologic features of cutaneous crateriform squamous cell proliferations were studied. Two hundred twenty cases of wholly excised crateriform squamous cell proliferations were studied both clinically (age, sex, location, and duration) and histologically (hematoxylin-eosin-stained sections). For comparison, we studied 100 consecutive cases of wholly excised noncrateriform squamous cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…As reported, these metastasizing KA could have been misdiagnosed as KA but are true SCC . In fact 10% as KA diagnosed tumors are malignant and progressing SCC . Hallmarks of malignant tumors such as, prominent mitoses or cytological atypia, are not observed in KA.…”
Section: Discrimination: Ka Versus Sccmentioning
confidence: 81%
See 2 more Smart Citations
“…As reported, these metastasizing KA could have been misdiagnosed as KA but are true SCC . In fact 10% as KA diagnosed tumors are malignant and progressing SCC . Hallmarks of malignant tumors such as, prominent mitoses or cytological atypia, are not observed in KA.…”
Section: Discrimination: Ka Versus Sccmentioning
confidence: 81%
“…If KA are truly able to form metastasis is still a matter of debate, in contrast with SCC which metastasize in up to 5% . As reported, these metastasizing KA could have been misdiagnosed as KA but are true SCC . In fact 10% as KA diagnosed tumors are malignant and progressing SCC .…”
Section: Discrimination: Ka Versus Sccmentioning
confidence: 95%
See 1 more Smart Citation
“…There are a variety of special stains or tests, including expression of lectins, proliferating cell nuclear antigen, vascular cell adhesion molecule (CD‐106) and intercellular adhesion molecule (CD‐54) adhesion molecules, angiotensin type 1 receptor expression, oncostatin M expression, syndecan‐1 expression, MIB‐1 immunohistometry, and stromelysin 3, and ultrastructural features said to be useful in distinguishing the KA from the SCC 48–64 . Sadly, none of the methods, including identification of basal cell carcinomas and KAs by fluorescent lectin staining of a tumor‐specific disaccharide, 49 has proven of practical value.…”
Section: Pathologymentioning
confidence: 99%
“…According to Sanchez Yus et al 48 at least 24% of KA showed malignant transformation into SCC. KA must be totally excised and studied for any evidence of malignancy.…”
Section: Introductionmentioning
confidence: 98%